2020
DOI: 10.1111/nph.16791
|View full text |Cite
|
Sign up to set email alerts
|

Dung mimicry: the function of volatile emissions and corolla patterning in fly‐pollinated Wurmbea flowers

Abstract: Summary It has been suggested that flowers of some angiosperms mimic vertebrate faeces (dung) in order to exploit insect pollinators that utilize faeces as a source of food and/or oviposition sites. We investigated a potential case of mimicry in Wurmbea elatior (Colchicaceae), a lily that exhibits a faecal odour and pattern of dark spots on the corolla. We found that W. elatior is pollinated by a broad assemblage of coprophagous flies and is dependent on pollinator visits for seed production. The flowers emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
(115 reference statements)
0
12
0
Order By: Relevance
“…Instead, we conclude, that wasps seem to be attracted to the studied plants by floral scent compounds that are also physiologically and/or behaviorally active for other flower visitors, such as bees, moths, butterflies, and flies (Andersson, 2003;Dötterl and Vereecken, 2010;Johnson et al, 2020;The Pherobase, 2020). The release of such compounds might be the reason that H. helix and H. sphondylium are attractive to insects of various orders and families.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Instead, we conclude, that wasps seem to be attracted to the studied plants by floral scent compounds that are also physiologically and/or behaviorally active for other flower visitors, such as bees, moths, butterflies, and flies (Andersson, 2003;Dötterl and Vereecken, 2010;Johnson et al, 2020;The Pherobase, 2020). The release of such compounds might be the reason that H. helix and H. sphondylium are attractive to insects of various orders and families.…”
Section: Discussionmentioning
confidence: 81%
“…Some EAD-active compounds of H. sphondylium are less common among the floral scents, especially the nitrogen-bearing 2-aminoacetophenone and its likely derivate m/z 120, 135, 92, 65, 163, 93 (Johnson et al, 2020). 2-Aminoacetophenone has been shown to attract various flies to bacteria (Kapsetaki et al, 2014), and its likely derivative is EADactive in the scent of fly-pollinated Wurmbea flowers, a lily that exhibits a fecal odor (Johnson et al, 2020). Moreover, the scent of H. sphondylium is reminiscent of the smell of dung, possibly because of the presence of p-cresol.…”
Section: Discussionmentioning
confidence: 99%
“…It is fairly common for fly‐deceiving flowers to offer food rewards. For example, nectar is present in the sexually deceptive flowers of Gorteria diffusa (Ellis & Johnson, 2010) and in some dung‐ or carrion‐mimicking flowers (Shuttleworth et al ., 2017; Johnson et al ., 2020). In these systems, the mimetic floral signals are irresistible to the flies and the role of the nectar is to manipulate the flies' behaviour to maximize the probability of pollen transfer.…”
Section: Discussionmentioning
confidence: 99%
“…revealed that variation in flower size and oligosulfide concentration was associated with niche partitioning between sarcophagid and calliphorid flies, which appear to specialize in dead animals of different sizes [ 90 ]. Subsequent studies in the same region revealed that flies attracted by scent are filtered as pollinators by non-chemical traits that either restrict access by size (floral guardrails [ 91 ]) or encourage landing by simulating the presence of other flies (tepal spots [ 92 ]).…”
Section: Discussionmentioning
confidence: 99%